Asuransi dan Koperasi Syariah di Indonesia: (Kajian Filosofis, Historis, Yuridis dan Sosiologis) - Wahyu Akbar; Anshary, A. Hafiz; Umar, Masyitah; Khasyi’in, Nuril (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
This paper aims to optimize Islamic insurance and cooperatives in Indonesia, reviewed from philosophical, historical, juridical and sociological studies. The method used is library research which examines literature analyzed qualitatively using a sociological, historical, juridical, and philosophical approach. The study results show that insurance and cooperatives carry the spirit of togetherness and help each other. The spirit of insurance and cooperatives is deeply rooted in Indonesian society; it's just that they are not institutionalized regularly. The Indonesian government is trying to accommodate insurance and cooperatives in various laws and regulations legally. However, there is still a need for firmness and clarity regarding the Sharia insurance and cooperatives law, especially if there is a dispute. In addition, insurance and cooperatives must improve their practice and understanding so that the community feels their benefits.